Nature and Super Natural Elements in Ruskin Bond’s Works: Exploring the World of Ruskin Bond: Nature, Supernatural, and Love (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In today's fast paced era of technological innovation and scientific intentions and discovery, dwelling upon the paranormal activities that results into horror sensation and scary feelings appears a bit unusual kind of task as to whether people in general are readily available to accommodate their open minds full of latest updates of world's smartest gadgets with those supernatural, mysterious and eerie kind of elements. It all seems credible when we come across Ruskin Bond's sharing his own experience of seeing the apparition of his late fatherAubrey Bond. Bond’s selected stories replete with elements of terror have undoubtedly been successful in drawing his peruses from that beautiful ambience of oak and pine and cedar to the mysterious woods witnessing the frightening environment full of creepy horrifying surroundings. Bond has given a realistic touch to the description of the scenario making the readers awestruck and his quality of making unbelievable a believable one made him the Connoisseur of the mysterious and macabre. Ruskin Bond has won the hearts of millions of readers with his countless charming short stories and introspective novels. From biographical tales about acting as a grandfather to children, to tales of unrequited love, the cross-cultural dimensions of Indian society, and the power and beauty of nature, Bond's more than forty novels and short story collections have made him an internationally acclaimed author. In Ruskin Bond's World, Indian scholar Gulnaz Fatma, Ph.D. sheds light on one of her country's greatest and most beloved storytellers, tracing the influences in his stories from a childhood in colonial India through his time spent in Britain and his life today among India's hills and mountains. She explores the biographical as well as the imaginary elements of his fiction and explores in detail the themes of nature, children, love, and animals in his novels and short stories.